Minat Mahasiswa Akuntansi untuk Memperoleh Sertifikasi Profesi Chartered Accountant (CA) - Sukmawati, Putu Sri; Suputra, I Dewa Gede Dharma (E-Jurnal Akuntansi, 2022)
Chartered Accountant (CA) is a professional path to become a professional accountant and accountant with international standards. The purpose of this study is to provide empirical evidence regarding the effect of the level of understanding, attitude, and motivation on the interest of accounting students to obtain the Chartered Accountant (CA) professional certification. The research was conducted at the Faculty of Economics and Business, Udayana University. The number of samples used as many as 85 samples, with non-probability sampling method using purposive sampling technique. Data was collected by means of a questionnaire. The collected data was then analyzed using multiple linear regression analysis techniques. The results showed that the level of understanding, attitude, and motivation had a positive and significant effect on the interest of accounting students to obtain professional certification of Chartered Accountant (CA). Keywords: Level of understanding; Attitude; Motivation; Student Interest; CA Certification.